US heavy cruisers 1941-45 : pre-war classes - Stille, Mark.; Wright, Paul, 1947- (Oxford : Osprey Publishing, 2014)
American Navy cruisers built prior to World War II saw extensive action throughout the Pacific War, in both surface actions like Guadalcanal, and carrier battles like Midway. Designed and produced under the regulations of the Washington Naval Treaty, the heavy cruisers of the Pensacola, Northampton, Portland, New Orleans and Wichita classes were exercises in compromise. While they possessed very heavy armament this came at the cost of protection. As the classes evolved, these flaws began to be corrected. Despite these drawbacks, the pre-war heavy cruiser classes served with distinction throughout World War II.
Pensacola Class -- Northampton Class -- Portland Class -- New Orleans Class -- Wichita Class.
Includes bibliographical references and index.
Keywords: 1900-1999; Cruisers (Warships) -- United States -- History -- 20th century; World War, 1914-1918 -- Naval operations, American; Military operations, Naval -- American; History